Industrial Production and Quality Control of Snake Antivenoms - León Montero, Guillermo (2014)
The production of snake antivenoms involves stages such as production of venom, immunization of animals to generate hyperimmune plasma, immunoglobulin purification, viral inactivation (or removal), and stabilization of the formulation. In order to manufacture products of satisfactory effectiveness and safety, antivenom design must be validated by preclinical and clinical studies. Moreover, during the industrial production, the quality of the products and of the entire manufacturing process (including management of clean rooms, production of water for injection, and sterilization or sanitization of the equipment) must be strictly evaluated. This chapter presents a practical description of the stages involved in the design, production, and quality control of snake antivenoms.